2019
DOI: 10.4490/algae.2019.34.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Ecklonia cava (Laminariales) and Sargassum horneri (Fucales) synergistically inhibit the lipopolysaccharide-induced inflammation via blocking NF-κB and MAPK pathways

Abstract: Ecklonia cava (EC) has been widely utilized as an ingredient in commercial products such as functional foods and cosmeceuticals. Recently it has been found that Sargassum horneri (SH) has been invading on Jeju Island coast area by its huge blooming. Moreover, both seaweeds are considering as important ingredients in traditional medicine specifically in East-Asian countries (China, Japan, and Korea). In the present study, we attempted to compare anti-inflammatory properties of 70% ethanolic extracts of EC (ECE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The general composition of seaweeds dried from HHGDM and FDM were analyzed according to the AOAC standard 2005 standards (AOAC Internationa l, 2005). The ash content of seaweed samples from the two different drying methods were measured by drying in a furnace at 550℃ for 6 h (Sanjeewa et al, 2019). Kjeldahl digestion method was used to determine the protein content of seaweed samples from HHGDM and FDM.…”
Section: Chemical Composition Analysismentioning
confidence: 99%
“…The general composition of seaweeds dried from HHGDM and FDM were analyzed according to the AOAC standard 2005 standards (AOAC Internationa l, 2005). The ash content of seaweed samples from the two different drying methods were measured by drying in a furnace at 550℃ for 6 h (Sanjeewa et al, 2019). Kjeldahl digestion method was used to determine the protein content of seaweed samples from HHGDM and FDM.…”
Section: Chemical Composition Analysismentioning
confidence: 99%
“…However, the accumulation and overproduction of NO and PGE 2 are indicative of chronic inflammation or cancer. It has been reported that different types of S. horneri ethanol extracts inhibit the overproduction of NO and PGE 2 in LPS-stimulated macrophage RAW264.7 cells [34,[42][43][44][45][46]. Moreover, treatment with ethanol extract of S. horneri was shown to decrease NO and PGE 2 levels in fine dust-induced RAW264.7 cells [47].…”
Section: Discussionmentioning
confidence: 99%
“…Marine algae are rich in functional ingredients such as polysaccharides, polyphenols, phytosterols, and carotenoids (Lee et al 2013, 2016, Shanura Fernando et al 2017, Asanka Sanjeewa et al 2019, Ding et al 2019, Dai et al 2020. Pyropia species, belonged to Bangiaceae family which are the most important perennial edible marine red algae, are cultivated and consumed in East and Southeast Asian countries such as Korea, Japan, and China.…”
Section: Analysis Of Biological Components In Pylpmentioning
confidence: 99%